'Working in the dark': Swedish general dental practitioners on the complexity of root canal treatment. (19th August 2016) - Dahlström, L.; Lindwall, O.; Rystedt, H.; Reit, C.
Abstract: Aim: To explore elements of reasoning and understanding that might obstruct the performance of good‐quality root canal treatment (RCT) and make general dental practitioners (GDPs) produce and accept root fillings of inferior quality. Methodology: The study was designed as a qualitative and explorative study based on seven videotaped focus group interviews analysed by means of qualitative content analysis. Nine predetermined questions were followed. Thirty‐three GDPs (4–6 dentists/interview), employed in the Public Dental Health Service in Gothenburg, Sweden, participated. Results: Feelings such as anxiety, frustration, stress or exhaustion were associated with RCT. In general, RCT was regarded as complex, mysterious and embedded in uncertainty. A feeling of loss of control was frequently described in relation to all procedural steps from negotiating the canal to prognostic deliberations. Reasons could include challenging canals, complicated instruments and the fact that treatment had to be performed in a concealed space without visible insight. Several dentists questioned the requirements for correctly performing RCT, and some indicated that striving towards optimal technical root filling quality should not be expected in each case in general practice. Most of the GDPs were unable to complete a case within the remuneration system, and they therefore either spent more time than the set fee allowed for or accepted a suboptimal root filling when the time limit was reached. Conclusions: High levels of stress and frustration in relation to RCT were reported by the GDPs. RCT was regarded as complex and was often performed with an overall sense of lack of control.